Desain Pendidikan Agama Dalam Keluarga Guna Membangun Kemampuan Problem Solving Anak - Kusroh Lailiyah; M. Syamsul Rizal; Farah Dzil Barr (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2020)
The purpose of this study is to discuss how to design religious education in the family to build children's problem solving abilities. The location of this research is Pekalongan U tara District, Pekalongan City. The approach in this research uses a descriptive approach, the method used is a combination of qualitative and quantitative methods. A qualitative approach is used to describe trends in religious education, while the quantitative method, namely statistical testing, includes hypothesis testing on signs, hypothesis testing through the khai-squared distribution and hypothesis testing on the median value. Based on the hypothesis testing on the median value, it was found that the type of application of religious education is actually the same through (exemplary, habituation and training, advice, supervision, and punishment). Meanwhile, based on testing the distribution of the khai-squared preference in applying among the applications of religious education, it is actually the same. The qualitative conclusion is that the pattern of religious education in families in Pekalongan Utara District, Pekalongan City, has mostly implemented a permissive pattern, while the design of religious education that is appropriate in order to build problem solving abilities is in accordance with the social conditions in which the adolescent lives. Keywords: Religious education design, parenting style, problem solving